Clean utilization of lignite to produce biomethane by optimizing the microbial community. (1st January 2023) - Yang, Lin; Zhang, Yongfeng; Hao, Zhifei; Ding, Daqian; Liu, Zhanying
Abstract: Optimization of microbial community is requisite to boost methane production from inferior coal biodegradation. Here is reported an efficient method of converting lignite into methane by microorganisms, which takes lignite as substrate and obtains efficient microbial flora from sludge by means of enrichment and domestication. The Single Factor Experiment and Response Surface Methodology were carried out to regulate the operating conditions and optimize the medium. The results showed that the optimized gas production of biodegradable lignite reached 79.29 mL (54.32% methane)/2 g coal, which is much higher than the other microbial conversions of lignite to methane reported to date. Furthermore, the combined most probable number counting method and high-throughput sequencing technique revealed that the main bacteria in the fermentation process are acid forming bacteria, sulfate-reducing bacteria and methanogenic bacteria. This study provides new insight into methanation and the clean utilization of lignite. Graphical abstract: Image 1 Highlights: Biogas production was enhanced, and the anaerobic fermentation time was shortened. Stable and efficient microflora was obtained through subculture and domestication. Biomethane was greatly improved after optimization of medium. The bacterial community structure is changing at fermentation different stages.